Do the nutrient compositions and mineral matter contents of meagre (Argyrosomus regius) vary depending on the rearing environment? - Hamzaçebi Sevim; Öztürk Fatma (Oceanological and Hydrobiological Studies)
This study aimed to compare the nutrient compositions and element contents of meagre (Argyrosomus regius) reared in different environments. The biochemical analyses revealed that the ash contents of cage and earth pond-cultured fish were higher than that of wild fish (p < 0.05), while there were also significant differences in the protein, fat and moisture contents (p > 0.05). The cage-reared fish had the lowest Ca, Mg, P and S levels, while the highest levels were determined in wild fish. The highest Fe, Se and Mn levels were determined in the earth pond-reared fish. Wild fish had the lowest Fe, Zn, Se and Cr levels, while the lowest Cu and Mn levels were determined in the cage-reared fish. The cage-reared fish had the highest Zn, Cr and Ni levels. Wild fish were determined to contain high levels of As, Hg and Pb. The earth pond-reared fish had a high Cd level, while having lower As and Hg levels than those of fish reared in other environments. As a result, farmed meagre are thought to be affected by the metal content in both the feed and the water. The results of the study showed that the content of the meagre flesh varied depending on the rearing conditions.